Manejo Agronómico del cultivo de Sábila Aloe Vera y sus procesos agroindustriales - Sempertegui Cabero, Manuel de Jesús (2020)
SUMMARY "Agronomic management of the cultivation of Aloe Vera and its agro-industrial processes" This work consisted of describing how the producers of the aloe cultivation carry out the agronomic management of the same in order to subject this product to agro-industrial processes for its commercialization. By analyzing the information obtained from the various researches reviewed, it is recognized that there is a commercially attractive market for this product, due to the versatility of the product, farmers can obtain a wide portfolio of clients. In conclusion, it can be said that in Ecuador this crop is planted in the Santa Elena area for commercial purposes and that from this experience technical information has been gathered regarding the agronomic management of this crop, as well as their experiences in exporting it. Based on these premises, it is recommended that farmers apply for credit to the public area, in order to have other income alternatives, also recommending experimental and scientific research through the production of this product